Kajian Analisis Kelayakan Pengembangan Tanpa Dan Dengan Pembangunan Jalan Baru (Studi Kasus Jl. Bayangkara Penunahan Alam Sutra Tangerang Pasca Pengoperasian Exit Toi Jakarta - Merak Km 15+400) - Mutharuddin, Mutharuddin; Muhammadun, H. Haris (Warta Penelitian Perhubungan, 2010)
Central and lard garemment's ofTangerang Qty and PT (psero) Jasa Marga as toll rood ~tor magreed q:xming Jakarta-Merak exit toll road in km 15+500 which amnecting Bayangkara street, BouJemrstreet of Alam Sutra Residential and Rm;a Serpong Street as main node at Alam Sutera Roundabout. Theeksisting of toll rood exit will i11l]Xld to land u~ as along the rood. Dereloping will also effect to traffic'JXlformaru:e at Bayangkara street around that road after ~ting of Jakarta-Merak toll road link in Km15+400. I71e problem is whether the rood reasonable to derelop eamomically not only benefit but alsoadvantage. Another problem is to find out the advantage of amtribution with and without dereloping.Methodology of this studtj is traffic suroci; method with four step planning analysis model (trip generation,trip attraction, modal split and traffic assignment) and eamomic analysis. Finally, The result of the studyprovide that dereloping of Bm;angkara street is reasonable with tloo alterna~s which are enrouragingBayangkara street step btJ step become ROW 15;20;24 and without amstructing new rood. Eren though,with Bayangkara street extending offer mare Wiefit than without amstructing new rood.Keyword: FeasibilihJ, expen~, benefit, VOE, alternative election